(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
This article reveals the trends in the development of an Agile-based project management system at food production enterprises. Recently, the food industry has undergone a complete transformation in project management. Food industry enterprises have begun to implement flexible methodologies such as Agile in order to increase their adaptability and competitiveness in a rapidly changing market. Agile allows you to quickly respond to the rapidly changing requirements of consumers, as well as legislation in the food industry, allowing you to quickly respond to new market conditions and optimize the processes of the enterprise.